1990
DOI: 10.1063/1.345358
|View full text |Cite
|
Sign up to set email alerts
|

Particle and power balances of hot-filament discharge plasmas in a multidipole device

Abstract: This paper considers particle and power balances to estimate the bulk plasma potential of a hot-filament discharge plasma produced in a multidipole plasma device. The bulk plasma potential dependence on positive dc bias applied to an anode is analyzed, and the predicted characteristics of the plasma potential are compared to the experiment. It is shown that the plasma potential can be more positive or more negative than the anode bias potential. When the potential is more negative, a steady-state potential dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 8 publications
2
34
0
Order By: Relevance
“…10. 20 For curve A no insulator was present while for curve B the insulator was present. That result was attributed to the presence or absence of the insulator.…”
Section: -5mentioning
confidence: 99%
“…10. 20 For curve A no insulator was present while for curve B the insulator was present. That result was attributed to the presence or absence of the insulator.…”
Section: -5mentioning
confidence: 99%
“…Some important different aspects of a hot-filament discharge were elaborated by Cho et al [5] in their work on the influence of a positively biased electrode on the plasma potential. They used a closed set of charge, particle and energy balance equations in order to extract particular information concerning the plasma potential as a function of the anode bias potential.…”
Section: Introductionmentioning
confidence: 99%
“…Doubleplasma devices are far from being understood, although there exists an extensive body of empirical data on the behavior of the main plasma parameters as functions of the external conditions. The latter are, e.g., the wall geometry and surface conditions [2], effects of mechanical and electrical supports and additional electrodes [5], probes [6], additional wire grids for electron heating [7], electrostatic confinement grids [8], the filament cathode arrangement and temperature [2], the ionizing electron beam energy, the magnetic cusp geometry [3,9] and magnetic field strength [10], effects of secondary electrons emitted from the walls [11] and other supplementary electron beams [12,13,14], the type of the gas used [3], etc.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that a positively biased wire grid can serve either to control the plasma potential [2], or to raise the electron temperature [3]. Large probes and anodes were used for driving the plasma potential [4] and for producing anode-type double layers [5,6,7].…”
Section: Introductionmentioning
confidence: 99%